Sistem Informasi Izin Online Berbasis Web Menggunakan Framework Codeigniter - Rizki Wahyu Nugroho; Teguh Andriyanto; Rini Indriati (Generation Journal, 2022)
So far, the absence of work permit that is still valid until now is consodered inefficient, when an employee want to apply for leave of absence from work, the employee must first come to the office, then ask or approval from his superiors and the application letter is approved and then printed as evidence. The purpose of this study is to make easier for employee to apply for leave absence from work online and to help manage employee data and data for an absent work permit automatically enter the Development Sector. The system development model in this study is the Waterfall Model. Software testing is carried out using User Acceptance Testing (UAT). Data collection techniques used in this study were observation, interviews and documentation. The application used to support sending notifications is the Whatsapp API. This system is built using sublime text 3 editor and uses the PHP as programming language and MySQL as database management. The final result of this research is an online validation system or submitting a permit for not going to work.